DEVELOPMENT AND TESTING OF A CAPACITIVE DIGITAL SOIL MOISTURE METRE (Nigerian Journal of Technology, 2016)
This paper presents a low cost, simple digital soil moisture meter, working on the principle of dielectric. A digital soil moisture meter using the NE555 timer and micro controller as a major electronic component was developed and tested, which display its output in a range of 0.0 to 99% on the 7-segment displayed unit. The digital soil moisture meter developed was compared with gravimetric method for soil moisture determination on fifteen soil samples added different level of water during calibration process. The results revealed a relatively linear relationship between the moisture content process and the digital soil moisture meter. The regression coefficient (R2) of the digital soil moisture meter calibration was 0.984. Twenty soil samples were used in validation of the calibrated digital soil moisture meter. The regression coefficient (R2) was found to be 0.964, showing validity of the developed digital soil moisture meter. The developed meter provided up to 96% accuracy in estimating the value of the soil moisture content. The results showed that the developed digital soil moisture meter is more reliable, sensitive, precise and easy to use. http://dx.doi.org/10.4314/njt.v35i3.30